Pengaruh model pembelajaran discovery learning berbantuan video dan problem based learning terhadap motivasi dan hasil belajar siswa - Mira Wabula; Pamella Mercy Papilaya; Dominggus Rumahlatu (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2020)
The low motivation and cognitive learning outcomes of students can be caused by errors in the selection and use of learning models in the class. This study aims to determine the effect of discovery video learning and problem-based learning model (pbl) on motivation and learning outcomes of class X students of SMA Negeri 1 Ambon. The research method used was a quasi-experimental research design using a pretest posttest nonequivalent control group design. The sample used was grade X MIPA-6 and X MIPA-7 students. The instrument used was a questionnaire containing 30 items to measure motivation and 60 multiple choice questions to measure cognitive learning outcomes. Motivational data and student learning outcomes were analyzed with the ANCOVA test. The results showed that there was no effect of the discovery-assisted learning model and the pbl learning model on student motivation (p > 0,05). But there is an influence of learning models of learning with the help of the discovery and pbl learning models on cognitive learning outcomes (p < 0,05). The conclusion of this study, the discovery learning model and pbl learning model do not affect motivation but affect cognitive learning outcomes